Application of Benson Relaxation Therapy in Type 2 Diabetes Patients with Nursing Problems of Blood Glucose Level Instability - Hikmah, Dafiyatil; Sudarso, Sudarso; Yosdimyati, Leo; Camelia, Dina (Jurnal Keperawatan Profesional, 2025)
Blood glucose instability is a variation in blood glucose levels that rise or fall from the normal range. Signs and symptoms that may appear include polyphagia, polydipsia, polyuria, drowsiness, dizziness, coordination disorders, and low or high blood glucose levels. Benson relaxation therapy is one non-pharmacological intervention that has been proven effective in helping to control blood glucose levels. This study aims to determine the application of Benson relaxation therapy in patients with type 2 diabetes mellitus with blood glucose level instability nursing problems. Methods: This study used a case study with a nursing care approach on two respondents with type 2 diabetes mellitus. Results: Before the intervention, both patients complained of frequent thirst, frequent urination, and frequent hunger. After the Benson relaxation therapy intervention was conducted routinely for 7 consecutive days, with each session lasting 10-15 minutes, there was a decrease in blood glucose levels in both respondents. Conclusion: This study found that Benson relaxation therapy is effective as a complementary intervention to help stabilise blood glucose levels while improving patients' psychological well-being.